Ứng dụng chu tuyến vào việc loại bỏ đối tượng nhỏ trong quá trình véc tơ hoá tự động - Toàn, Đỗ Năng (Journal of Computer Science and Cybernetics, 2016)
In this paper, we describe a method of using contours to delete small objects for improving feature images. In general, small objects are holes or noises. Therefore, they can be detected and filled or deleted easily by using our method without patterns in automatic vectorizing process. Besides, the paper also shows. types of maps that can be vectorized and have been verified by using this method in MAPSCAN software package that has been developed in the Oepartment of Pattern Recognition and Knowledge Engineering such as: - Topography, hydrography and transports maps etc. - Technical, designing, electronic circle drawings and finger images etc.